Explaining Student Character Formation: The Mediating Mechanism of Classroom Climate in Muhammadiyah Schools - Nurul Latifatul Inayati; Istanto Istanto; Muhammad Zidan Nur Ihsan; Ma’ruf Alfattah; Siti Rosilawati Ramlan (Jurnal Pemberdayaan Masyarakat, 2026)
The phenomenon of declining discipline and increasing juvenile delinquency in West Java poses serious challenges to the formation of student character. This study aims to analyze the influence of Muhammadiyah learning and teachers’ attitudes on students’ character by considering the role of mediation in the classroom climate. This study used an exploratory quantitative approach with 319 respondents selected through purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) and Bootstrap tests based on the Correlated Bias (BCA). The results of the study show that Muhammadiyah learning has a significant effect on the classroom climate (p=0.021), but it does not affect students' character (p=0.196). Teachers' attitudes have a significant effect on classroom climate (p0.001) and students' character (p0.001). In the mediation test, the classroom climate did not mediate the relationship between Muhammadiyah learning and character, but did partially mediate the relationship between the teacher’s attitude towards the student's character and the student’s character. These findings confirm that character formation is more effectively influenced by the quality of teachers’ pedagogical relationships and classroom climate, thereby strengthening theories about the effectiveness of character education in educational contexts and the role of contextual relationships in these contexts.